2004
DOI: 10.1002/jsfa.1782
|View full text |Cite
|
Sign up to set email alerts
|

Texture and distribution of pectic substances of mango as affected by infusion of pectinmethylesterase and calcium

Abstract: Fresh cut mangos were infused with pectinesterase (PME) and calcium chloride, and the effect on textural properties, distribution of pectic substance and degree of esterification was determined. Temperature gradient infusion with PME and/or calcium chloride increased gumminess and chewiness, but had no impact on hardness and adhesiveness. The distribution of pectic substances, as protopectin or alkaline soluble pectin, was approximately twice that of water-or chelator-soluble pectin. The degree of esterificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
4
16
0
2
Order By: Relevance
“…The enzymatic activity of this variety of mango was low and similar to Keitt variety mango puree where levels of activity up to 12.6 ± 1.1 UPME/g have been reported (Banjongsinsiri et al, 2004;Jamsazzadeh Kermani et al, 2015). Low activity (4.5 UPME/100 g of pulp) was found in Zebda variety mango.…”
Section: Enzymatic Mango Extractssupporting
confidence: 72%
See 1 more Smart Citation
“…The enzymatic activity of this variety of mango was low and similar to Keitt variety mango puree where levels of activity up to 12.6 ± 1.1 UPME/g have been reported (Banjongsinsiri et al, 2004;Jamsazzadeh Kermani et al, 2015). Low activity (4.5 UPME/100 g of pulp) was found in Zebda variety mango.…”
Section: Enzymatic Mango Extractssupporting
confidence: 72%
“…In this regard, it should be noted that the technological problems in citrus juice associated with PME have been attributed to a high molecular weight thermostable fraction, which is also crucial in the establishment of pasteurization values in orange juice (Versteeg et al, 1980). Several studies have reported a low enzyme activity in mango PME when compared to citruses and other fruits (Banjongsinsiri et al, 2004;Duvetter et al, 2009;Jamsazzadeh Kermani et al, 2015). Likewise, PME with different activities or characteristics has been reported in mango skin and pulp (Labib et al, 1995;Lizada, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in accordance to Gil et al (1996), who indicated that TSS and TA increased significantly in arils of different pomegranate genotypes during storage. Banjongsinsiri et al (2004) concluded that TSS content of "Kent" mango is most likely moderated by changes in the solubility of large molecular weight insoluble pectin and nonpectin components, such as cellulose and hemicellulose, in the cell wall. Furthermore, Ghasemnezhad et al (2013) also found that TSS and TA content of both chitosan-coated and uncoated pomegranate arils gradually increased during 12-day storage at 4°C.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses were conducted in triplicate on the enzyme extract at 25°C. Briefly, PME activity was measured potentiometrically by measuring free carboxyl groups formed as a result of enzyme action on pectin (Banjongsinsiri et al, 2004). The reaction mixture in the standard method assay consisted of 5 mL of PME sample and 50 mL of a 1% citrus pectin solution containing 0.1 M NaCl.…”
Section: Respiratory Rate and Ethylene Productionmentioning
confidence: 99%